Impact of level of expertise versus the statistical tool on vertebral fracture assessment (VFA) readings in cohort studies. Issue 2 (February 2017) - Aubry-Rozier, B.; Fabreguet, I.; Iglesias, K.; Lamy, O.; Hans, D.
Abstract Summary The present study tested if the accuracy of the VFA reading reproducibility is more affected by the statistical tool used or by the reader's level of expertise in 50 VFA from a population-based cohort, the OstéoLaus study. We found that uniform kappa and instruction reading with the ISCD/IOF VFA reading course both increased the accuracy of the reproducibility. Introduction Vertebral fractures (VF) due to osteoporosis are under diagnosed. Screening osteoporosis in the general population allows improving management of fragility fracture. It consists to perform a dual X-ray absorptiometry and a spine X-ray to look at a VF. To reduce the dosage of radiation, prevalent or incident VF could be detected by DXA image. The aim of the present study was to test the reproducibility of vertebral fracture assessment (VFA) readings in a population-based cohort and to explore if the accuracy of the reproducibility is more affected by the statistical tool used or by the reader's level of expertise. Methods We calculated the reproducibility of VFA reading by uniform and Cohen's kappa, comparing one expert and one non-expert, before and after an instructional on-line International Society of Clinical Densitometry (ISCD) /International Osteoporosis Foundation (IOF) course on VFA reading. We performed the analysis on 50 VFA from a population-based cohort, the OstéoLaus study. Results Before the VFA reading course, reproducibility with Cohen's kappa was moderate to poor (0 to 0.520), good with the uniform kappa (0.796 to 0.958). After the course, both Cohen's kappa and uniform kappa statistically increased, ranging from 0.524 to 1.000. Conclusions For female population-based cohort studies, we recommend using the uniform kappa and instructing a non-expert reader using the ISCD/IOF VFA reading course to correctly read and evaluate the reproducibility of the VFA reading.